Removal of heavy metals from motorcycle washing wastewater using a zeolite-embedded sheet - Takarina, Noverita Dian; Ambarsari, Hanies; Pramudyawardhani, Sekar Arum; Rahmawati, Maria Fatima Niken Kris; Johan, Erni; Matsue, Naoto; Adidharma, Mohammad Afdhal (Makara Journal of Science, 2025)
The increased use of motorcycles for transportation has heightened environmental challenges related to their washing, particularly the discharge of untreated wastewater containing heavy metals, such as copper (Cu) and lead (Pb), into drainage systems. This study explored the effectiveness of zeolite-embedded sheets (ZESs) in the removal of these pollutants from motorcycle washing wastewater. ZESs were prepared through treatment of nonwoven sheets with Linder Type A (LTA Zeolite) powder and heat treatment, washing, and drying. Characterization was performed via scanning electron microscopy with energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy. Over a 60 min adsorption period, the ZES achieved removal efficiencies of 40% for Cu after 30 min and 70% for Pb after 60 min. The results confirm that ZESs are a promising adsorbent for heavy-metal remediation and particularly effective for lead removal in motorcycle washing wastewater.